Medial Prefrontal Cortex Processes Threatening Stimuli in Juvenile Rats - Kabitzke, Patricia A (Nature Publishing Group, 2014)
To survive, all mammalian species must recognize and respond appropriately to threatening stimuli. In adults, the prelimbic medial prefrontal cortex (mPFC) appears to be involved in fear expression, whereas the infralimbic mPFC mediates fear extinction. In juvenile rats (PN26), the mPFC receives information on potential predators but does not act on it. To test whether the prefrontal cortex is capable of fear regulation in the young organism, we exposed juvenile rats to a threatening or nonthreatening stimulus and assessed fear and brain Fos activation of the mPFC subdivisions, amygdala and periaqueductal gray (PAG). In response to the threat, juveniles froze more, spent more time far from the threat, and had elevated numbers of Fos-positive cells in the prelimbic mPFC, the medial amygdala, and ventral PAG. To test the hypothesis that the mPFC has a dual role in modulating the amygdala and PAG in juveniles, we pharmacologically disinhibited each of the two subdivisions of the mPFC and assessed freezing and downstream activation to the threat. Juvenile rats infused with picrotoxin into the prelimbic mPFC and exposed to a threatening stimulus froze less, spent less time far from the threat, and increased Fos expression. Infusion of picrotoxin into the infralimbic mPFC also reduced fear responding to the threatening stimulus but had no effect on Fos expression. In sum, it appears that the mPFC can process threatening stimuli in juveniles at this age, even though it is normally not involved in the fear responses.